The Role of Incentives in Increasing Employee Engagement at CV. Asstro Tarogong Garut - Nuroni, Andri Muhamad; Padilah, Nopia Nur (Golden Ratio of Data in Summary, 2023)
In the increasingly competitive era of globalisation, companies need to ensure a high level of employee engagement to maintain productivity and work quality. This study aims to analyse the effect of incentives on employee engagement at CV Asstro Tarogong Garut. This type of research is quantitative with descriptive and associative approaches. The population in this study were all 34 employees of CV Asstro Tarogong Garut. The sampling technique used total sampling, so the number of samples used was 34 employees. The research was conducted at CV Asstro Tarogong Garut which is located in Tarogong Kaler, Garut Regency. The results showed that incentives have a significant effect on employee engagement, with a considerable contribution in increasing employee engagement. Providing good incentives can encourage employees to be more committed and motivated in their work. The implications of this study provide recommendations for companies to continue to develop effective incentive systems and pay attention to other factors that can affect employee engagement such as organisational culture and work environment.